2009
DOI: 10.1038/aps.2009.42
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin inhibits CYP3A4 activity in vitro and in vivo

Abstract: Aim:To investigate the inhibitory interactions of bufalin and CYP3A4. Methods: Recombinant human CYP3A4 was incubated with bufalin in vitro. Bufalin was administered ig and iv to Wistar rats to further estimate its impact on CYP3A4, and midazolam was given to index the activity of CYP3A4. Results: The IC 50 of bufalin was 14.52 μmol/L. Bufalin affected CYP3A4 activity with increases in AUC 0-t and t 1/2 , and decreases in CL and the formation of 1-hydroxy-midazolam after ig or iv administration of midazolam (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Molecules like curcumin, kaempferol, and silibinin have appeared in thousands of scholarly articles, many investigating the molecular targets through which these molecules act (Table ). Over 10 000 targets have been identified, with the purified TCM components typically acting in the 1 to 200 μM concentration range (Table ). Intriguingly, the targets reported for even a single compound are often unrelated. For instance, curcumin has been reported to inhibit calcium-dependent ATPase, HIV-1 and HIV-2 proteases, human growth factor receptor 2 (HER2), protein kinase A (PKA), protein kinase C (PKC), lipoxygenase, P450 enzymes, tyrosinase, and thioredoxin reductase, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules like curcumin, kaempferol, and silibinin have appeared in thousands of scholarly articles, many investigating the molecular targets through which these molecules act (Table ). Over 10 000 targets have been identified, with the purified TCM components typically acting in the 1 to 200 μM concentration range (Table ). Intriguingly, the targets reported for even a single compound are often unrelated. For instance, curcumin has been reported to inhibit calcium-dependent ATPase, HIV-1 and HIV-2 proteases, human growth factor receptor 2 (HER2), protein kinase A (PKA), protein kinase C (PKC), lipoxygenase, P450 enzymes, tyrosinase, and thioredoxin reductase, among others.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that ArBu entered the blood rapidly and was detected only after 2 min CYP3A4 was the major metabolic enzyme of bufogenins. Since bufalin was a strong inhibitor of CYP3A4 ( Li et al, 2009 ), ArBu with the same parent nucleus was likely to inhibit CYP3A4. In combination with the results from the heart rate test, it was found that the rats’ heart rates in the 60 mg/kg ArBu-administrated group increased significantly at T max .…”
Section: Resultsmentioning
confidence: 99%
“…CYP3A4 accounts for ~40% of the total cytochrome P450 in human liver microsomes and metabolizes >50% of the clinically used drugs 19. Earlier research has also shown that bufalin had a modest but significant inhibition of CYP3A4 enzyme both in vitro and in vivo 20. As a result, the high CYP3A4 enzyme metabolic capability in liver would be a probable explanation for the extremely high concentration of bufalin and [ 18 F]fluoroethyl bufalin in liver.…”
Section: Discussionmentioning
confidence: 99%